Epigenetic pathways in hematological malignancies (Hematology Meeting Reports, 2009)
It has been recognized for many years that tumors develop as a result of accumulated molecular-genetic or genomic alterations. However, cancer development is not restricted to the genetic changes, but also to epigenetic changes. The inheritance of information based on gene expression levels in known as epigenetics, as opposed to genetics, which refers to information transmitted on the basis of gene sequence. To date, DNA methylation and the post-tranductional modifications of histone proteins are the best studied epigenetic modifications.